External Evaluation of the Independent Evaluation Office. (Policy Papers; Policy Paper ;, 2013)
We have been asked by the Executive Board of the International Monetary Fund to undertake an external review of the activities of its Independent Evaluation Office (IEO). This is the second such evaluation in the IEO's twelve year history. The first review, led by Karin Lissakers (the 'Lissakers Report'), was presented to the Board in 2006. That report considered the extent to which the Office had succeeded during its first five years of operation in fulfilling its mandates and made recommendations to enhance its role within the IMF's institutional architecture. Our report thus focuses on IEO activities since 2006. As set out in the terms of reference of our Panel (see Appendix I), the central objective of this report is to evaluate how well the IEO has met its institutional mandates. The terms of reference, while not constraining the range of issues we could consider, also asks that we 'assess the IEO's effectiveness along several dimensions, including: (i) the appropriateness of evaluation topics; (ii) the independence of the IEO; (iii) the cost-effectiveness of the IEO and its operations; and (iv) the appropriateness and adequacy of the evaluation process including, but not limited to, how IEO recommendations are endorsed by the Board and implemented.'.